2018
DOI: 10.1161/strokeaha.118.022129
|View full text |Cite
|
Sign up to set email alerts
|

Recanalization in Cerebral Venous Thrombosis

Abstract: Background and Purpose-The role of recanalization of the occluded dural sinus or vein in the outcome of patients with cerebral venous thrombosis (CVT) is not established. We aimed to systematically review, in patients with CVT, (1) the recanalization rate and its association with (2) clinical outcome and (3) CVT recurrence. Methods-Systematic search in MEDLINE (Medical Literature Analysis and Retrieval System Online), Cochrane Library, and clinicaltrials.gov (inception to September 2017). We considered cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
3
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 31 publications
5
52
3
5
Order By: Relevance
“…Similarly to our patient, Verma et al described early recanalization of venous sinuses thrombosis with protein S deficiency after 15 days of anticoagulant therapy [4]. According to data available in the literature, a high recanalization grade of CVST independently predicts positive neurological outcome [15], while lack of venous recanalization is associated with worse clinical outcome [16]. A study on 50 subjects indicated that patients with multiple sinus thromboses have a higher case fatality rate [17].…”
Section: Discussionsupporting
confidence: 67%
“…Similarly to our patient, Verma et al described early recanalization of venous sinuses thrombosis with protein S deficiency after 15 days of anticoagulant therapy [4]. According to data available in the literature, a high recanalization grade of CVST independently predicts positive neurological outcome [15], while lack of venous recanalization is associated with worse clinical outcome [16]. A study on 50 subjects indicated that patients with multiple sinus thromboses have a higher case fatality rate [17].…”
Section: Discussionsupporting
confidence: 67%
“…More than 80% of CVT patients achieved recanalization, either complete or partial, which was associated with a good functional recovery [27,28]. However, it is still unclear whether the lack of recanalization should influence anticoagulant treatment duration, as the evidence on its correlation with CVT recurrence was scarce [28].…”
Section: Prognosismentioning
confidence: 99%
“…Furthermore, other prognostic factors have been suggested in a single-center cohort study on 81 patients, which brought up a cardiac marker, plasma cardiac troponin (cTn) elevation as a poor prognostic factor of CVT (89). There have been a limited number of studies suggesting venous recanalization as a surrogate biomarker for functional outcomes in CVT (90).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there was a statistical relationship between clinical outcomes and recanalization. However, it is required to collect further data to ascertain the need for recanalization in patients under anticoagulant therapy with a clinical resolution of the symptoms (90).…”
Section: Discussionmentioning
confidence: 99%